Operation Barbarossa [videorecording (DVD)] - Batty, Peter, 1931- (Shanachie, 2004)
A background to Hitler's attack on the Soviet Union on June 22, 1941. This battle on the Russian front led to the biggest, bloodiest battle ever fought, costing the lives of at least 20 million people and ending Europe's dominance in world affairs. In sheer numbers, miles of front, and quantity of guns, shells, and tanks, no other battle in history can compare with it. Codenamed "Operation Barbarossa" by the German Army, the footage shown has been obtained from both sides and includes notable eyewitness accounts from surviving members of Hitler's inner circle.